Cardiometabolic risk profile of participants with prediabetes diagnosed by HbA1c criteria in an urban Hong Kong Chinese population over 40 years of age. Issue 9 (6th February 2015) - Woo, Y. C.; Cheung, B. M. Y.; Yeung, C. Y.; Lee, C. H.; Hui, E. Y. L.; Fong, C. H. Y.; Tso, A. W. K.; Tam, S.; Lam, K. S. L.
Abstract Aims To investigate the usefulness of the additional measurement of HbA1c, compared with performing only the oral glucose tolerance test (OGTT), in identifying participants at increased cardiometabolic risk, in an urban Chinese population. Methods All participants from the fourth visit of the population‐based Hong Kong Cardiovascular Risk Factors Prevalence Study, without known diabetes, were included. All had their glycaemic status assessed by OGTT and HbA1c, according to American Diabetic Association 2010 criteria. Results Based on OGTT criteria alone, 3.5% of the study cohort (N = 1300) had diabetes and 19.2% had prediabetes. Based on HbA1c criteria only, 6.2% had diabetes and 61.2% had prediabetes. The measurement of HbA1c, in addition to the OGTT, increased the proportion of participants with diabetes to 7.8% and with prediabetes to 65.3%. Subjects with prediabetes having raised HbA1c but normal glycaemia (N = 600) had waist circumference, systolic blood pressure, fasting glucose, insulin resistance index (HOMA–IR), Gutt Index and Framingham 10‐year cardiovascular risk scores intermediate between those with both normal HbA1c and glycaemia (N = 350), and those with impaired fasting glucose and/or impaired glucose tolerance (N = 249; all P < 0.01). Conclusion The measurement of HbA1c in our population, in addition to the OGTT, results in the detection of a large number of participants with prediabetes having raised HbA1c but normal glycaemia who have a cardiometabolic risk profile intermediate between impaired fasting glucose and/or impaired glucose tolerance and normal participants, and would benefit from early lifestyle intervention.